Converting the threats of fossil fuel-based energy generation into opportunities for renewable energy development in India - Singh, Mukesh Kumar; Malek, Javed; Sharma, Harish Kumar; Kumar, Rahul (Renewable energy, 2024)
Many researchers and non-governmental organizations have raised concerns about environmental degradation in developing nations. India is also one of the developing nations primarily dependent upon conventional energy resources to meet the energy demand of the exponentially increasing population. India has a tremendous reserve of renewable energy, which can satisfy the increasing energy demand of the nation. Being at an emerging stage, India needs to identify the significant enablers that can empower renewable energy development. Interpretive Structural Modeling (ISM) has been employed to represent the interrelationships among the enablers by developing a hierarchy structural model. The driving and dependence powers of the enablers are calculated by integrating the fuzzy concept with the Matrix Impact of Cross Multiplication Applied to Classification (MICMAC) technique. Global pressure for cleaner energy, increasing price of fossil fuels, and rising energy demand with the population can act as the most significant enablers. The present study is one of the preliminary studies that has converted current fossil fuel-based energy generation threats into opportunities for renewable energy development. The developed structural model of the enablers would represent hierarchical strategies at different stages for developing renewable energy in developing nations.